(untitled) (AYUSHDHARA, 2023)
Padmak Agad is indicated in all types of Luta and Keet Visha. According to Acharya Vagbhatta, heaviness in head and eyes, coma, dizziness, dyspnoea, pain, swelling, fever, itching and anorexia are common symptoms of all Keeta Damsha. Several synthetic and plant origin analgesic are being tested for their efficacy and potency on different animal model including hot plate, tail flick, tail clip, cold pain, filament pain, tail immersion technique, acetic acid induced writhing test, formalin induced writhing test etc. Material and Methods: Tail clip model and Hot plate model were selected for the present study. Eighteen Swiss albino mice had been divided in to three groups each group contain six mice. First group was negative control group; second group was test drug group while third group was standard group. Test drug was given to the group 2 for 7 days O.D. Result: When we performed the tail clip test, response time of group 1, 2, 3 were 4.40±1.853, 14.07±9.309, 40.68±11.759 seconds respectively. In Hot Plate model, calculated response time of group 1, 2, 3 were 2.93±0.667, 5.46±0.911, 6.04±0.857 seconds respectively. When we used Dunnett’s multiple comparisons test to compare the group 1 to group 2 and group 1 to group 3, there was statistically no significant role of test drug in tail clip model and hot plate model. Discussion and Conclusion: No effect of Padmak Agad is found in tail clip model. Padmak Agad is effective in hot plate model but not up to significant level.